LEGAL BUDAYA MASYARAKAT HINDU DESA ADAT WANGAYA GEDE MENCEGAH DEFORESTASI - Wibawa, I Putu Sastra (Jurnal Hukum Agama Hindu Widya Kerta, 2018)
Preventive measures to prevent deforestation are made through the establishment of the rule of law and enforcement. However, this is not considered effective enough in maintaining the forest. Required improvement of legal culture of the community, especially about the legal awareness of Hindu communities around the forest area of Mount Batukaru in the management and protection. Protection of forest sustainability is inadequate. There is only the role of law enforcement and good rule of law, but also requires the role of a good legal culture so that the law can be effective to implement. This research is qualitative with approach of socio-legal research with descriptive analysis.